GAMBARAN KARAKTERISTIK IBU DALAM PEMANFAATAN PENOLONG PERSALINAN DI WILAYAH KERJA PUSKESMAS GUNUNG BARINGIN KECAMATAN PANYABUNGAN TIMUR KABUPATEN MANDAILING NATAL TAHUN 2012 - Abdul Wahab (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2013)
Abstract Delivery period is one period of a risk for pregnant women when experiencing complications that may increase the risk of maternal mortality and infant mortality if not getting a healthy delivery assistance. However, the use of delivery assistance by health personnel in the community is still very low due to the phenomenon of deliveriesperformed by midwives. This research was aims to describe the characteristics of mothers in birth attendant utilization in wilayah kerja Gunung Baringin Kecamatan Panyabungan Timur Kabupaten Mandailing Natal Tahun 2012. Using a descriptive survey design method that aims to describe maternal characteristics (age, education, occupation, income,parity), the believe, knowledge and attitude of mothers in birth attendant utilization using univariat analysis using questionnaires of 57 respondents were selected by purposive sampling . The results showed that respondents Faith In Childbirth Attendant Utilization in the category of poor ie 22 people (38.6%), knowledge of the respondents were in the category of bad 35 people (61.4%). The attitude of the respondents in the category of bad 30 people (52.6%), utilization Labor Helper respondents using traditional birth attendants (not health) more that 36 people (63.2%) than with the use of doctors,midwives, nurses (medice) that 21 people (36.8%). There should be communication / outreach to the public on an ongoing basis on the utilization of health workers in rural optimally through health education provided in the activity perwiritan mothers.